ETHANOL EXTRACTS OF PROPOLIS (EEP) AGAINST LYMPHOCYTE ACTIVATION CELLS IN HEALTHY MICE (Mus Musculus) BALB/C - Rohmawati, Emi (Biotropika: Journal of Tropical Biology, 2014)
Propolis is a substance like glue formed by honey bees from resin of plant which has the ability to stimulate immune system. The purpose of this study is to determine the ethanol extract of propolis on the activity of lymphocytes in healthy Balb/c mice and to asses the optimum dose administration of EEP for lymphocyte activation in Balb /c mice. Methods: mice was aclimate for two weeks, mice control without treatment EEP and a other was treated with EEP dependent dose, doseÂ 1 (50 mg/ kgBW),Â dose 2 (100 mg/kgBW), and dose 3 (200 mg/kgBW). Spleen was isolated and to find out the amount of lymphocyte we analyzed with flow cytometry. Parameter measured in this experiment is quantitative by measuring relative number of T cells that consist of CD4+CD62L+, CD4+CD62LË, CD8+CD62L+, dan CD8+CD62LË. Then data was analyzed by SPSS 16.0 software for windows with ANOVA test and advanced by Tukey test and Gomes-Howell with an interval 0.05 is used. The result showed that ethanol extract of propolis can activate CD4 T cells so that CD4 T cell lost CD62L molecule and turned into T cells CD4+CD62LË. Ethanol extract of propolis can enhance proliferation of naÃ¯ve type of CD8 T cell, so that the number of T cell memory (TCM) decreased. Dose of 100 mg/kgBW of ethanolic propolis extract spatially act as immunostimulant for CD4+CD62LË activation, while the dose of 200 mg/kgBW act asÂ immunosuppressant in the same cells. Key words: T cell activation, Â propolis, Balb/cÂ mice.